Is There More Violence in the Middle?. Issue 3 (8th June 2018) - Jones, Zachary M.; Lupu, Yonatan
Abstract: Is there more violence in the middle? Over 100 studies have analyzed whether violent outcomes such as civil war, terrorism, and repression are more common in regimes that are neither full autocracies nor full democracies, yet findings are inconclusive. While this hypothesis is ultimately about functional form, existing work uses models in which a particular functional form is assumed. Existing work also uses arbitrary operationalizations of "the middle." This article aims to resolve the empirical uncertainty about this relationship by using a research design that overcomes the limitations of existing work. We use a random forest‐like ensemble of multivariate regression and classification trees to predict multiple forms of conflict. Our results indicate the specific conditions under which there is or is not more violence in the middle. We find the most consistent support for the hypothesis with respect to minor civil conflict and no support with respect to repression.